Pengaruh Penggunaan Media Audio Visual Flash Player terhadap Hasil Belajar Mata Pelajaran PKn di Sekolah Dasar - Shellyn Roudhotul Apriana; Feri Tirtoni (Edudikara: Jurnal Pendidikan dan Pembelajaran, 2022)
The purpose of this study was to determine student learning outcomes using audio-visual media flash player in 4th grade PKN elementary school learning, because at this time students' interest in learning about PKN and the Pancasila values ​​contained therein greatly decreased. It is hoped that foreign cultures that enter the era of globalization will not make the next generation of the nation forget their own culture, so that PKN SD learning is very important to be applied from an early age. This study uses experimental quantitative methods, researchers use experimental quantitative methods because the data obtained is more accurate, and in order to find out whether the audio visual flash player learning media can improve student learning outcomes and increase student learning motivation or not. In addition, this research is also expected so that students can understand and apply the values ​​contained in PKN SD subjects through audio-visual flash player learning media, if students are able to understand and apply the material that has been delivered. Then the goals of education will be achieved properly, and teacher educators are able to create the next generation of the nation who has Pancasila values, loves the homeland, has a sense of unity and integrity, has religious values ​​and norms contained in PKN subjects, so that HR (Human Resources and Human Resources) ) that exist in this nation are increasingly qualified and able to compete with other countries.